RUANG KITA DAN RESILIENSINYA KINI DI TENGAH PANDEMI - Yusfan Adeputra Yusran (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
This pandemic time has forced us to redefine the meaning of the space. There are many things that make us have to change the way we did in our daily lives. From how to dress, worship, eat at restaurants, queue to buy tickets, meetings, until when we return home after doing activities outside. This paper aims to provide an overview of the current crisis related to spatial experiences by reviewing current issues regarding the impact of the pandemic on architectural aspects and urbanism. Descriptively, interdisciplinary studies related to pandemics are discussed and juxtaposed by looking at several topics of local resilience in the Nusantara. The people of the Nusantara have various ways to survive, but it seems that the pandemic requires us to change our mindset about how architectural and city planning prioritizes health factors and is resilient to current conditions, because this is not the first time and (it seems) will repeat itself. And architecture cannot respond this alone.